Caracterização do conteúdo de fossas e tanques sépticos na cidade de Natal - Santos, Yannice Tatiane da Costa (2009)
Only 32% of the population of Natal is attended by sewage, while the remaining population use pits and septic tanks. The characterization of the contents of septic tanks and pits contributes to the performance of such system and may guide the decision on treatment of these contents. The main of this research is to characterize the contents of interior residential pits and septic tanks in the greater Natal, with the following specific goals: to develop and manufacture a sampler capable of collecting a representative sample of the entire column (the surface scum, the clarified liquid and sludge bottom); to compare the contents of the tanks with the pits; to compare the contents of the septage from vacuum trucks; to relate the composition content with socioeconomic characteristics of households; to compare the content in both chambers of the septic tanks in series; to assess the situation of the content before and six months after the cleanness; and ultimately propose a pilot scale plant for treatment of septage. Once the sampler was developed, samples were collected within 14 septic tanks and 10 pits in many districts of Natal. Medians of the 24 systems were obtained: temperature, pH, conductivity, oil and grease, total solids, total suspended solids and sediments of 28.0 °C, 6.95; 882 mS/cm, 75.2 mg/L; 10,169 mg/L, 6,509 mg/L and 175 mL/L respectively; 111.0 mgN/L for ammonia, 130.5 mgN/ L for organic nitrogen, 0.2 mgN/L for nitrite, 0.4 mg/L for nitrate; 8935 mgO2/L for COD, 29.2 mgP/L for total phosphorus, thermotolerant coliforms from 9.95 E +06 CFU/100mL helminth eggs and 9.2 eggs/L with a maximum concentration of 688 eggs/L and minimum of 0 eggs/L. Medians of organic nitrogen and TKN were significantly different between groups of tanks and pits. The systems with cleanness gap from 11 and 20 years presented the higher concentrations for most variables. The effluent from the toilets and bathrooms participate more effectively in contributing fractions of solids, alkalinity, nitrogen, COD, total phosphorus, thermotolerant coliforms and helminth eggs. The systems used by socioeconomics class with income from R$ 3,700.00 to R$ 7,600.00, presented higher concentrations for COD, nitrogen, solids and helminth eggs. The first of the two chambers had always presented higher concentrations over the second compartment. The analysis of variance for most variables, showed that the values of septic tanks, pits and septage from vacuum trucks belong to the same group. In the samples taken after cleanness, the median of pH and temperature increased, while alkalinity, COD, organic nitrogen, total phosphorus, ammonia and helminth eggs decreased. The oils and greases and thermotolerant coliforms had slightly varied due to the continuous release of sewage into the systems that maintained their steady state concentrations.